Poligami Indonesia dan Maladewa: Sebuah Perbandingan atas Keberanjakan Hukum Keluarga Islam - putri, suci ramadhani; Yulinda, Deva; Arqurnain, Weis (MAHAKIM Journal of Islamic Family Law, 2023)
This article aims to provide an overview of Indonesia and the Maldives as well as the development of Islamic family law in each country, then compare the provisions of polygamy in both countries, both the similarities and the differences. This is followed by analyzing the changes in polygamy provisions that have occurred in the two countries. This article is qualitative research that uses library research. The primary data source for this research is the laws and regulations in both countries that regulate polygamy. The secondary data source is any literature that is relevant to this research. These various data were analyzed using deductive analysis techniques. Legal reforms in the realm of Islamic family law have been carried out by many Muslim countries in the world, including Indonesia and the Maldives. Even though Indonesia and the Maldives share the majority of the Syafiʽi sect, both of them have various differences as well as various similarities regarding the provisions of polygamy. These differences are inseparable from various factors, such as history and geographical location; legal system; social, economic, and cultural; gender relations; and development of family law. This article argues that the Islamic family law reform method for the topic of polygamy in Indonesia tends to apply both intra-doctrinal reform and extra-doctrinal reform. The Maldives tend to only apply the extra-doctrinal reform.